Finite element modelling on shear behaviour of concrete beam reinforced with glass fiber reinforced polymer bars system / Nurul Izziyante Mat Noor - Mat Noor, Nurul Izziyante (2013)
The computational simulating of reinforced concrete beam reinforced by glass fibre reinforced polymer (GFRP) bars subjected to static loading dependent on the modelling of nonlinear constitutive laws of materials by using LUSAS 14.7 Modeller. Nonlinear behaviour of GFRP bar reinforced concrete beam includes shear cracking where static loading introduces further complexities, such as stiffness degradation in concrete. In this paper, the reliability of presented constitutive models for concrete by using Drucker-Prager Plasticity Model when subjected to static loading that considers stress distribution is investigated. In the analysis of reinforced concrete structures, a number of diverse approaches have been used for material modelling. These include of nonlinear elastic models where this simulation is related to constitutive models based on elasticity approach. For these aims, finite element (FE) models will be developed in eight numbers of specimen beam models by having o f steel rebar and GFRP as reinforcing bars. The results that will be subtracted from FE analysis will be discussed and reviewed with the results of experimental tests investigated later in laboratory.